UMP offers Science and Technology Foundation Programme - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 25 March 2022 - Universiti Malaysia Pahang (UMP) is offering a Science and Technology Foundation Programme that will provide opportunities for students interested in pursuing their studies in premier programmes such as the UMP-Karlsruhe University of Applied Science (HKA) Germany dual degree programme and the UMP-China dual degree programme.